3009 Understanding the Lived Experience of Deaf Dominicans: Implementing Qualitative Methods with the Deaf Community in the Dominican Republic. (27th March 2019) - Mora, Joshua; Taveras, Pablo; Estill-Varner, History; Sanchez, Jose Javier; Hall, Wyatte; Tavarez, Zahira Quinones; Batista, Edward; Jesurum, Alan; Siddiqi, Shazia; Dye, Timothy
Abstract : OBJECTIVES/SPECIFIC AIMS: Qualitative approaches help explore poorly understood phenomenon, and are highly engaging, enabling both sides of an encounter greater connection. Historically, Deaf communities have been marginalized and oppressed, with their linguistic needs unrecognized and ignored. As a result, Deaf participants are rarely involved in clinical research. Like other marginalized communities, the Deaf community experiences health disparity compared with others, especially in low- and middle-income settings. The purpose of this project was to assess the feasibility of conducting qualitative research with Deaf Dominicans. METHODS/STUDY POPULATION: We implemented a partnered research process with 59 Deaf community members in the Dominican Republic, conducting preliminary thematic analysis through reviews of interviews and on-site debriefings. RESULTS/ANTICIPATED RESULTS: Participants were highly engaged with the Deaf-Deaf research encounters, indicating satisfaction with both the process and with the opportunity to communicate their needs and interests. Preliminary findings indicated Deaf Dominicans were highly engaged, confirming their interest, and often stated that they felt they were being listened for the first time. Indeed, some participants claimed that this was the first time they communicated their experiences as Deaf Dominicans and appreciated the opportunity to relate this experience to Deaf interviewers. DISCUSSION/SIGNIFICANCE OF IMPACT: This experience confirms that the Deaf Dominican community can be mobilized and will participate in Deaf-Deaf research.